Single cell transcriptomics in blood of patients with chronic obstructive pulmonary disease - Yeonjeong Heo; Jeeyoung Kim; Seok-Ho Hong; Woo Jin Kim (BMC Pulmonary Medicine)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. Single-cell RNA sequencing (scRNA-seq) provides gene expression profiles at the single-cell level. Hence, we evaluated gene expression in the peripheral blood of patients with COPD. Methods Peripheral blood samples from seven healthy controls and eight patients with COPD were obtained in this study. The 10X Genomics Chromium Instrument and cDNA synthesis kit were utilized to generate a barcoded cDNA library for single cell RNA-sequencing. We compared the scRNA-seq data between the COPD and control groups using computational analysis. Functional analyses were performed using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. Results scRNA-seq was used to analyze the transcriptome of peripheral blood mononuclear cells from seven normal controls and eight patients with COPD. We found an increased number of monocyte/macrophages in the COPD group compared to the normal control group. Among the differentially expressed genes (DEGs) in monocyte/macrophages, we identified 15 upregulated genes (EGR1, NR4A1, CCL3, CXCL8, PTGS2, CD83, BCL2A1, SGK1, IL1B, BTG2, NFKBIZ, DUSP2, MAFB, PLAUR and CCL3L1) and 7 downregulated genes (FOLR3, RPS4Y1, HLA-DRB5, NAMPT, CD52, TMEM176A and TMEM176B) in the COPD group compared to the normal control group. Conclusions Using scRNA-seq, we found differences in cell type distribution, especially in monocyte/ macrophages. Several upregulated and downregulated genes were found in the monocyte/macrophages of the COPD group.